Penerapan Model PBL Pada Materi Aturan dan Tempat Bermain yang Aman Untuk Meningkatkan Literasi Sains dan Teknologi di Kelas 1C Di SDN Kauman 1 Kota Malang - Laili, Maghfirotul; Restian, Arina; Kumalasari, Ratna Nur (J-SES : Journal of Science, Education and Studies, 2025)
This study aims to explore the implementation of Problem-Based Learning (PBL) on the topic of "Rules and Safe Play Areas" to enhance science and technology literacy among first-grade students in class 1C at SD Negeri Kauman 1. The research uses a Classroom Action Research (CAR) design, conducted in two cycles involving planning, implementation, observation, and reflection. The results show that the application of PBL significantly increases student engagement and understanding of science concepts related to safety in play. In the first cycle, students faced challenges in connecting scientific concepts with real-life safety rules. However, improvements were made in the second cycle, where clearer connections were established, leading to better participation and understanding. The study concludes that PBL can effectively improve science and technology literacy in early-grade students.